A Study of Government Cloud Adoption: The Australian Context - Busch, Peter; Smith, Stephen; Gill, Asif; Harris, Pedro; Fakieh, Bahjat; Blount, Yvette (ACIS, 2014)
The literature is scant around the take up rates of cloud computing by organisations. Cloud computing is nonetheless expected to be a major computing paradigm in the future. The benefits of the cloud vis-à-vis outsourcing many current in-house IT services and applications – both hardware and software based, are numerous. However, governments and many enterprises are still relatively unclear on the motives for adopting cloud technologies and the consequent benefits gained in a real-world operational environment. This paper examines the results from a survey conducted at a forum of senior government IT managers and their views towards cloud computing adoption. The paper provides insights both from technological and non-technological perspectives in the overall context of cloud adoption in Australian government enterprises.